Experimental and theoretical investigations on axial bearing capacity of steel angle members with local corrosion on their limb peaks. (11th January 2023) - Luo, Zhicheng; Li, Qiyu; Xu, Congbai; Hu, Hao; Zhang, Dachang; Han, Xingning
Highlights: Twenty-one steel angle members were locally corroded using the mechanical drilling method. The failure mechanism of the corroded steel angles was observed and analysed by tests and simulations. The effect of corrosion length, corrosion width, and slenderness ratio on the residual bearing capacity was investigated. A simplified method was proposed to calculate the residual bearing capacity of the corroded steel angles. Abstract: To investigate the effect of local corrosion damage on the bearing performance of steel angle members, a total of 21 specimens, with various slenderness ratios and corrosion levels, were prepared and subjected to axial compression. During the test, the load–displacement curves, load–strain histories, failure modes, and residual bearing capacity of the steel angles were experimentally obtained and analysed. After that, the finite element analysis (FEA) model, calibrated by the test results, was established to further reveal the failure mechanism of the corroded steel angles under axial compression. It was found that all the corroded steel angles finally failed under global buckling around the weak axis induced by local buckling, and their residual bearing capacities were negatively correlated with the widths and lengths of the local corrosion zones. However, for the angles with a large slenderness ratio or with a local corrosion length larger than 20% of the whole length, the effect of local corrosion on the residual bearing capacity gradually diminished. By using the equivalent cross-sectional area, a simplified design method was also proposed to evaluate the residual bearing capacity of the corroded steel angles, and the predictions agreed well with both the test and simulation results.